2013
DOI: 10.1111/cas.12212
|View full text |Cite
|
Sign up to set email alerts
|

CD169‐positive macrophages in regional lymph nodes are associated with a favorable prognosis in patients with colorectal carcinoma

Abstract: CD169 (sialoadhesin) is a sialic acid receptor that is expressed on specific macrophages such as lymph node sinus macrophages. Animal studies have suggested that CD169 + macrophages have a pro-inflammatory property, however, the role of these cells in human diseases has not been clarified. In our in vitro experiments with human macrophages, pro-inflammatory cytokines, such as type 1 interferon, induced strong expression of CD169, suggesting that CD169 might be a specific marker of inflammatory macrophages. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
116
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(132 citation statements)
references
References 33 publications
15
116
1
Order By: Relevance
“…Type I interferon, such as IFN-α, is known to induce CD169 expression in macrophages, 19 and we initially confirmed that IFN-α enhanced CD169 expression in HMDMs (Fig. 1B).…”
Section: Effects Of Natural Compounds On Cd169 Expression In Hmdmssupporting
confidence: 67%
See 2 more Smart Citations
“…Type I interferon, such as IFN-α, is known to induce CD169 expression in macrophages, 19 and we initially confirmed that IFN-α enhanced CD169 expression in HMDMs (Fig. 1B).…”
Section: Effects Of Natural Compounds On Cd169 Expression In Hmdmssupporting
confidence: 67%
“…19 Patients with a higher density of CD169-positive macrophages showed a significantly better overall survival than those with a lower density. 19 These observations suggested that elevated CD169 expression in sinus macrophages was closely associated with the induction of anti-tumor immune responses and exerted a beneficial effect on the clinical course. 19 Similar observations were subsequently observed in patients with melanoma, endometrial cancer, and breast cancer.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous reports, CD169 protein was mainly expressed on CD68 C Mf in the LN sinus. 27,35 Interestingly, multi-staining confocal microscopy analysis revealed a certain proportion of CD169 C cells were CD3 C CD8 C T cells (Fig. 1A and S2).…”
Section: Cd169 C Cd8 C T Cells Accumulate In Regional Ln and Decreasementioning
confidence: 96%
“…[21][22][23][24][25] A recent study demonstrated that CD169 C Mf could effectively generate CTL responses by cross-priming CD8 C T cells, which in turn, conferred immunity against re-exposure to the malignant cells. 26 The expression of CD169 in tumor-draining LN and its association with survival in CRC patients has been recently reported 27 ; however, the specific composition and function of CD169 C cells in tumor-draining LNs of cancer patients remain largely unknown. In the current study, we addressed this issue in CRC and identified a novel T cell subset, CD169 C CD8 C T cells.…”
Section: Introductionmentioning
confidence: 99%